Interest rate lift-off in the US: Moderate impact to date but emerging markets should brace themselves - Christoph Große Steffen (DIW Economic Bulletin, 2016)
For the first time in almost a decade, the US Federal Reserve raised interest rates at the end of 2015 - an initial step toward normalizing monetary policy which has been very expansive since the onset of the financial crisis. Ahead of the move, it was feared that the interest rate reversal might have a considerable impact on emerging markets because the hike would lead to more capital flows being diverted to the US. The present study concludes that this was not in fact the case: greater turbulence on the financial markets failed to materialize immediately after the first rate hike and the financing conditions for emerging markets did not initially deteriorate significantly. However, the interest rate will be raised further. In order to come through the contractionary cycle of US monetary policy unscathed, emerging economies with large current account deficits or those dependent on commodity exports in particular should brace themselves for possible fallout.
Keywords: E5; F3; F4; 330; US monetary policy; Emerging markets